MAIT cell activation in adolescents is impacted by bile acid concentrations and body weight. (17th February 2020) - Mendler, A.; Pierzchalski, A.; Bauer, M.; Röder, S.; Sattler, A.; Standl, M.; Borte, M.; von Bergen, M.; Rolle‐Kampczyk, U.; Herberth, G.
Summary: Bile acids (BAs) are produced by liver hepatocytes and were recently shown to exert functions additional to their well‐known role in lipid digestion. As yet it is not known whether the mucosal‐associated invariant T (MAIT) cells, which represent 10–15% of the hepatic T cell population, are affected by BAs. The focus of the present investigation was on the association of BA serum concentration with MAIT cell function and inflammatory parameters as well as on the relationship of these parameters to body weight. Blood samples from 41 normal weight and 41 overweight children of the Lifestyle Immune System Allergy (LISA) study were analyzed with respect to MAIT cell surface and activation markers [CD107a, CD137, CD69, interferon (IFN)‐γ, tumor necrosis factor (TNF)‐α] after Escherichia coli stimulation, mRNA expression of promyelocytic leukemia zinc finger protein (PLZF) and major histocompatibility complex class I‐related gene protein (MR1), the inflammatory markers C‐reactive protein (CRP), interleukin (IL)‐8 and macrophage inflammatory protein (MIP)‐1α as well as the concentrations of 13 conjugated and unconjugated BAs. Higher body weight was associated with reduced MAIT cell activation and expression of natural killer cell marker (NKp80) and chemokine receptor (CXCR3). BA concentrations were positively associated with the inflammatory parameters CRP, IL‐8 and MIP‐1α, but were negatively associated with the number of activated MAIT cells and the MAIT cell transcription factor PLZF. These relationships were exclusively found with conjugated BAs. BA‐mediated inhibition of MAIT cell activation was confirmed in vitro . Thus, conjugated BAs have the capacity to modulate the balance between pro‐ and anti‐inflammatory immune responses. Abstract : Schematic summary of the data from the present investigation in LISA study samples of 15‐year‐old children (n = 82). Conjugated but not unconjugated bile acids were associated with a lower MAIT cell activation and a higher inflammation (CRP, IL‐8 and MIP‐1α). Body weight was associated with MAIT cell activation as well as with MIP‐1α and IL‐8 concentrations but not with bile acid concentrations.